Errors in positioning of borehole measurements and how they influence seismic inversion. (11th August 2022) - Fernandes, Iris; Mosegaard, Klaus
Abstract: Inversion of seismic data using information from horizontal wells is often hampered by cumulative well‐location errors. These errors can have a significant influence on the final subsurface model derived from the data. To achieve a proper data integration and arrive at correct uncertainty estimates, we formulate the problem in a fully probabilistic framework and present a numerical approach for improving subsurface imaging using uncertain well‐log data and their uncertain locations as well as uncertain seismic data. The result is improved model error quantification in the seismic inversion process.